Role of Rajaswala Paricharya on Artavadushti w.s.r to Menstrual Disorders- A Holistic Approach - Diksha Udaipure; Aswathy K; Sucheta Ray; Priyanka Hajare (AYUSHDHARA, 2024)
In Ayurveda, "Rajaswala Charya" refers to the specific regimen or lifestyle guidelines designed for women during menstruation (Rajaswala). This term consists of various practices and recommendations aimed at supporting women’s health and well-being during their menstrual cycle. Unfortunately, it has been observed that the Rajaswala Paricharya is neither being publicized nor followed by the women in today era. As a result, there is need to educate the females, regarding the Rajaswala Paricharya (ways of living) recommended by Ayurveda to keep the Dosha in balance, which maintains health. Ayurveda advises women to adhere to "Paricharya" conduct that should be followed at various stages of life, such as Rajaswala, Garbhini, and Sutika, in order to improve their health and quality of life. The Rajaswala Paricharya is the one that receives the least attention. This subject was chosen because it was noted that modern science has described fatigue and lower abdomen pain as having an impact on the menstrual cycle and its related symptoms, although Ayurveda has not specified such symptoms. To achieve conception Acharya Susrutha has described four essential factors for fertility, Ritu, Kshetra, Ambu, Beeja. The females took part greater role in the formation of offspring because these four factors are related to them. Ayurveda gives prime importance to preventive aspects and elaborates “Rajaswala charya” or the care during menstrual cycles and during menarche in a female to prevent and cure gynaecological disorders. Due to adoption of western culture, females opt to attend programs they also prefer for parlours facial during Raja strava kala, which is prohibited by Acharya. Due to high mental pressure because of work load, family stress, competitive behavior in every place, more expectations lead to stress in her life.